Pemanfaatan tepung pisang menjadi produk olahan - Pince Salempa; Hasri Hasri; Sulfikar Sulfikar (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partners are the Community in the Tonyamang Village, Patampanua Sub-District, Pinrang Regency. The problem is: 1) Increased banana production results in a surplus or excess of bananas, 2) The lack of public knowledge about processing bananas into banana flour, and 3) The yields of abundant banana farmers have not been able to raise the economy of the community. The method used is: lecture, demonstration, discussion, and question and answer. The results achieved are abundant banana products that can be processed into banana flour which can be utilized as a variety of processed products that have economic value so that they are not only finished products (direct consumption).